Criminal law policy and inactive legal rules of Special part of the Criminal Code of the Republic of Belarus - Moroz, Dmitriy G. (Journal of the Belarusian State University. Law, 2021)
One of the destructive factors of the criminal law policy is the presence in the legislation of inactive norms of the Special part of the Criminal Code of the Republic of Belarus. One of the first Belarusian scientists who investigated this problem was professor I. I. Gorelik. On the basis of the historical analysis of the inactive legal rules of the Special part of the Criminal Code of the Republic of Belarus, carried out by I. I. Gorelik, and the modern analysis, the ratio of the applied and inactive legal rules of the Special part of the Criminal Code of the Republic of Belarus in judicial practice is determined the ratio of active and inactive legal rules. The classification of the inactive legal rules of the Special part of the Criminal Code of the Republic of Belarus and the reasons for the inaction of these norms are established. The negative consequences of the inactive legal rules of the Special part of the Criminal Code of the Republic of Belarus on the criminal law policy of the state and the main directions for eliminating these consequences are determined.